FAKTOR FAKTOR YANG MEMPENGARUHI KETERLAMBATAN PENETAPAN ANGGARAN PENDAPATAN DAN BELANJA DESA - Bambang Udiono (JI@P, 2021)
This study aims to describe and analyze the factors that influence the delay indetermining the Village Revenue and Expenditure Budget. The type of researchused is qualitative research with the opinion theory of Subechan et al (2014) andNatalia Gradiana Aunsuni (2019). Indicators of factors that influence the delay indetermining the Village Revenue and Expenditure Budget are commitment factors,coordination factors, competency factors and infrastructure. Methods of datacollection are carried out through interviews, observation and documentation. Theresults showed that the delay in determining the Village Revenue and ExpenditureBudget that occurred in Wagir Lor Village, Ngebel District, Ponorogo Regency wasinfluenced by the Commitment of the Village Head and Village Consultative Bodywhich was still not optimal, the coordination of the Village Head with the Deviceswas not fully running well, the Competence of Village Officials showed some stilldo not understand their main duties and functions, the existence of Village OfficeFacilities and Infrastructure is an important factor in the activities of implementingVillage Government.Keywords: Commitment, Coordination, Competence, Infrastructure.